Calidad espacial y análisis territorial de datos climatológicos: el caso del Estado de México - Díaz Delgado, Carlos; Iturbe Posadas, Antonio; Mamadou Bá, Khalidou; Reyna Sáenz, Francisco (CIENCIA ergo-sum, 2017)
-